Change in glycaemic control with structured diabetes self-management education in urban low-resource settings: multicentre randomised trial of effectiveness - Roberta Lamptey; Mary Amoakoh-Coleman; Mary Moffett Barker; Samuel Iddi; Michelle Hadjiconstantinou; Melanie Davies; Daniel Darko; Irene Agyepong; Franklyn Acheampong; Mary Commey; Alfred Yawson; Diederick E. Grobbee; et al. (BMC, 2023)
Abstract Background In high-resource settings, structured diabetes self-management education is associated with improved outcomes but the evidence from low-resource settings is limited and inconclusive. Aim To compare, structured diabetes self-management education to usual care, in adults with type 2 diabetes, in low-resource settings. Research design and methods. Design Single-blind randomised parallel comparator controlled multi-centre trial. Adults (> 18 years) with type 2 diabetes from two hospitals in urban Ghana were randomised 1:1 to usual care only, or usual care plus a structured diabetes self-management education program. Randomisation codes were computer-generated, and allotment concealed in opaque numbered envelopes. The intervention effect was assessed with linear mixed models. Main outcome: Change in HbA1c after 3-month follow-up. Primary analysis involved all participants. Clinicaltrial.gov identifier:NCT04780425, retrospectively registered on 03/03/2021. Results Recruitment: 22nd until 29th January 2021. We randomised 206 participants (69% female, median age 58 years [IQR: 49-64], baseline HbA1c median 64 mmol/mol [IQR: 45-88 mmol/mol],7.9%[IQR: 6.4-10.2]). Primary outcome data was available for 79 and 80 participants in the intervention and control groups, respectively. Reasons for loss to follow-up were death (n = 1), stroke(n = 1) and unreachable or unavailable (n = 47). A reduction in HbA1c was found in both groups; -9 mmol/mol [95% CI: -13 to -5 mmol/mol], -0·9% [95% CI: -1·2% to -0·51%] in the intervention group and -3 mmol/mol [95% CI -6 to 1 mmol/mol], -0·3% [95% CI: -0·6% to 0.0%] in the control group. The intervention effect was 1 mmol/mol [95%CI:-5 TO 8 p = 0.726]; 0.1% [95% CI: -0.5, 0.7], p = 0·724], adjusted for site, age, and duration of diabetes. No significant harms were observed. Conclusion In low-resource settings, diabetes self-management education might not be associated with glycaemic control. Clinician's expectations from diabetes self-management education must therefore be guarded.